2023
DOI: 10.3389/fcimb.2023.1217984
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile of human umbilical vein endothelial cells in response to coxsackievirus A10 infection reveals a potential role of miR-143-3p in maintaining the integrity of the blood–brain barrier

Abstract: Coxsackievirus A10 (CV-A10) has been one of the main etiologies of hand, foot, and mouth disease (HFMD) epidemics in recent years and can cause mild to severe illness and even death. Most of these severe and fatal cases were closely associated with neurological impairments, but the potential mechanism of neuropathological injury triggered by CV-A10 infection has not been elucidated. MicroRNAs (miRNAs), implicated in the regulation of gene expression in a post-transcriptional manner, play a vital role in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…divides the brain and spinal cord from the circulation. 88 While both viruses may infect and cross the human BBB, the outcomes of their The study also demonstrated that the exogenous hedgehog agonist S-Adenosyl-L-homocysteine can protect against meningitic E. colicaused BBB dysfunction. 90 Deterioration of the BBB is complex, including direct Human Immunodeficiency Virus infection of neurovascular unit cells, particularly pericytes and perivascular macrophages, as well as the release of pro-inflammatory cytokines and viral proteins from infected cells.…”
Section: Neuroinflammation and Its Role In Vzv Infection 41 | Blood-b...mentioning
confidence: 97%
See 1 more Smart Citation
“…divides the brain and spinal cord from the circulation. 88 While both viruses may infect and cross the human BBB, the outcomes of their The study also demonstrated that the exogenous hedgehog agonist S-Adenosyl-L-homocysteine can protect against meningitic E. colicaused BBB dysfunction. 90 Deterioration of the BBB is complex, including direct Human Immunodeficiency Virus infection of neurovascular unit cells, particularly pericytes and perivascular macrophages, as well as the release of pro-inflammatory cytokines and viral proteins from infected cells.…”
Section: Neuroinflammation and Its Role In Vzv Infection 41 | Blood-b...mentioning
confidence: 97%
“…91 According to research, coxsackievirus A10 (CV-A10) infection may cause differences in the way that microRNAs are expressed in human umbilical vein endothelial cells, which are essential for preserving the integrity of the BBB. 88…”
Section: Neuroinflammation and Its Role In Vzv Infection 41 | Blood-b...mentioning
confidence: 99%
“…The exosomes of EV71-infected RMS cells contain EV71 RNA, viral capsid protein VP1 and EV71 particles, which, partially resistant to antibody neutralization, can establish an effective infection in vitro ( Gu et al., 2020 ). However, exosomes of human oral epithelial cells infected with EV71 selectively package high levels of miR-30a, which can be delivered to macrophages and inhibit the type I IFN response by targeting the bone marrow differentiation factor 88 (MyD88), thereby enhancing viral replication ( Hu et al., 2023 ). It can induce the increase of exosomes secreted by colon cancer cell line HT29 and human mononuclear/macrophage cell line THP-1, meanwhile the EV71 virus nucleic acid carried in those exosomes can break through the limitation of virus-specific receptors and assemble its own genes into exosomes to expand the range of host infection ( Li et al., 2019 ).…”
Section: The Role Of Exosomes In Virus Infectionmentioning
confidence: 99%